Lithium ion battery
By coating the surface of lithium iron phosphate particles of the lithium iron phosphate particles of the lithium ion battery positive electrode material and adding organic boron additives to the electrolyte to form a boron-rich chemical battery interface, the side reaction problem of electrolyte caused by the high activity of the positive electrode material is solved, and the cycle stability is significantly improved and the self-discharge rate is reduced.
Patent Information
- Application Number
- CN202411533707.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-28
AI Technical Summary
The high activity of the positive electrode materials of existing lithium-ion batteries will bring side effects of the electrolyte, resulting in poor circulation stability and self-discharge rate.
Boron-rich chemical cell interface (CEI) is formed by coating the high-nickel material LiNixCoyMnzO2 on the surface of lithium iron phosphate particles and adding organic boron additives, such as isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxoborane, to the electrolyte, to form a boron-rich chemical cell interface (CEI) to inhibit the dissolution of nickel and the reaction of highly active Ni4+ valent substances with the electrolyte.
It significantly inhibits the dissolution of nickel, maintains the high nickel form, reduces the self-discharge rate, isolates the reaction between high-active Ni4+ valent substances and HF in the electrolyte, ensures circulation stability, and avoids continuous thickening through the dynamically repaired CEI film.
Smart Images

Figure BDA0005111779460000091 
Figure BDA0005111779460000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a lithium-ion battery. Background Art
[0002] At present, all applications of lithium iron phosphate materials involve coating the surface with conductive materials, mainly carbon-coated materials. When the coating layer is too thick, it will hinder the deintercalation of lithium ions, resulting in increased polarization, thereby reducing the capacity of the positive electrode material. The main shortcoming of lithium iron phosphate is its low energy density. It is necessary to develop a coating that has both high conductivity and avoids capacity loss caused by a reduction in the proportion of active materials. It has high ionic conductivity and improves rate performance, while not being affected by side reactions of the electrolyte due to high activity.
[0003] Lithium iron phosphate (LiFePO4), as a positive electrode material for lithium-ion batteries, has attracted widespread attention due to its excellent cycle life, safety performance and cost-effectiveness. However, the electronic conductivity and lithium ion diffusion rate of lithium iron phosphate are relatively low, which limits its performance in high-power applications. In order to improve the electrochemical performance of lithium iron phosphate, a common method is surface coating, such as carbon coating to improve its electronic conductivity. However, when the coating layer is too thick, it will hinder the intercalation and deintercalation of lithium ions, resulting in increased polarization, thereby reducing the capacity of the positive electrode material. The main shortcoming of lithium iron phosphate is its low energy density. It is necessary to develop a coating that has both high conductivity and avoids capacity loss caused by a reduction in the proportion of active materials. It has high ionic conductivity and improves rate performance. Summary of the invention
[0004] In view of this, the present invention is dedicated to providing a lithium ion battery to solve the problem in the prior art that the high activity of the positive electrode material of the lithium ion battery may cause the side reaction of the electrolyte.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] The present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material;
[0007] The positive electrode active material includes lithium iron phosphate particles and a coating layer coated on the surface of the lithium iron phosphate particles; the coating layer contains a high-nickel material, and the high-nickel material includes LiNi x Co y Mn z O2, where x+y+z=1, 0.80≤x≤0.95, 0.0 <y<0.20,0.0<z<0.20;
[0008] The electrolyte includes a positive electrode film-forming additive, and the positive electrode film-forming additive includes an organic boron additive.
[0009] Optionally, the D50 of the lithium iron phosphate particles is 0.7 to 6 μm, preferably 1 to 4 μm.
[0010] Optionally, the coating layer has a thickness of 0.5 to 3 μm, preferably 0.8 to 1.5 μm.
[0011] Optionally, based on the total mass of the positive electrode active material, the content of the lithium iron phosphate particles is 78-99.5wt%, and the content of the high-nickel material is 0.5-22wt%; preferably, based on the total mass of the positive electrode active material, the content of the lithium iron phosphate particles is 90-99wt%, and the content of the high-nickel material is 1-10wt%.
[0012] Optionally, the organic boron additive is selected from at least one of isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate), tetramethyl borate, trimethyl borate and trimethylcyclotriboroxane; preferably, the organic boron additive is isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane.
[0013] Optionally, based on the total volume of the electrolyte, the content of the positive electrode film-forming additive is 0.5 to 5 vol%, preferably 1.0 to 3 vol%.
[0014] Optionally, the electrolyte further includes an electrolyte, a negative electrode film-forming additive and an organic solvent; optionally, in the electrolyte, the molar concentration of the electrolyte is 0.1 to 4.0 mol / L; optionally, based on the total volume of the electrolyte, the content of the negative electrode film-forming additive is 0.5 to 5 vol%, preferably 1.0 to 3.0 vol%.
[0015] Optionally, the electrolyte is a lithium salt; optionally, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorobis(oxalatophosphate).
[0016] Optionally, the organic solvent includes at least one of carbonate solvents, carboxylate solvents, ether solvents, sulfone solvents, nitrile solvents, fluorinated carbonate solvents, fluorinated carboxylate solvents, fluorinated ether solvents and fluorinated sulfone solvents; preferably, the organic solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl formate, ethylene glycol dimethyl ether and fluoroacetonitrile.
[0017] Optionally, the negative electrode film-forming additive includes at least one of vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate and vinyl sulfate.
[0018] Through the above technical solution, the beneficial technical effects of the present invention are:
[0019] The lithium-ion battery of the present invention comprises a positive electrode active material, wherein the positive electrode active material can increase the proportion of active substances in the positive electrode material by coating lithium iron phosphate particles (LFP) with a high nickel material, thereby increasing the gram capacity of the LFP while increasing the conductivity, and at the same time using a low-cost organic boron additive as a positive electrode film-forming additive in the electrolyte, and having a higher occupied molecular orbital (HOMO) energy, can generate a boron-containing CEI (Chemical-Electrochemical Interface) before solvent decomposition, and in-situ formation of a boron-rich CEI on a high nickel interface can significantly inhibit the dissolution of nickel, maintain a complete high nickel form, reduce the self-discharge rate, and isolate highly active Ni 4+ The positive active material reacts with HF in the electrolyte to ensure cycle stability, and the formed CEI film is a dynamic repair process rather than continuous thickening. Applying the above positive electrode active material to lithium-ion batteries can give lithium-ion batteries good electrochemical properties.
[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0021] The present invention discloses a lithium-ion battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0022] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0025] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0026] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0027] In order to solve the problem in the prior art that the high activity of the positive electrode material of the lithium ion battery will bring about the side reaction of the electrolyte, the present invention adopts the following technical solution:
[0028] The present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material;
[0029] The positive electrode active material includes lithium iron phosphate particles and a coating layer coated on the surface of the lithium iron phosphate particles; the coating layer contains a high-nickel material, and the high-nickel material includes LiNi x Co y Mn z O2, where x+y+z=1, 0.80≤x≤0.95, 0.0 <y<0.20,0.0<z<0.20;
[0030] The electrolyte includes a positive electrode film-forming additive, and the positive electrode film-forming additive includes an organic boron additive.
[0031] The lithium-ion battery of the present invention comprises a positive electrode active material. The positive electrode active material can increase the proportion of active substances in the positive electrode material by coating lithium iron phosphate particles (LFP) with high nickel materials, thereby increasing the gram capacity of LFP while increasing the conductivity. At the same time, a low-cost organic boron additive is added to the electrolyte, and a higher occupied molecular orbital (HOMO) energy can be generated before the solvent is decomposed to form a boron-containing CEI. The boron-rich CEI is formed in situ on the high nickel interface, which can significantly inhibit the dissolution of nickel, maintain the complete high nickel form, reduce the self-discharge rate, and isolate the highly active Ni 4+ The positive active material reacts with HF in the electrolyte to ensure cycle stability, and the formed CEI film is a dynamic repair process rather than continuous thickening. Applying the above positive electrode active material to lithium-ion batteries can give lithium-ion batteries good electrochemical properties.
[0032] According to the present invention, the appropriate particle size of lithium iron phosphate particles has better gram capacity and better coating effect, and the technical effect is that if the particle size of the lithium iron phosphate particles is too small, the coating effect of the coating layer may be poor and the coating may be uneven; if the particle size of the lithium iron phosphate particles is too large, it may cause the internal Li to be difficult to escape and the gram capacity is low. The D50 of the lithium iron phosphate particles in the present invention can be 0.7 to 6 μm. Exemplarily, the D50 of the lithium iron phosphate particles can be any value among 0.7 μm, 1 μm, 2 μm, 4 μm and 6 μm, or any value within the range of any two of the above values. Preferably, the D50 of the lithium iron phosphate particles is 1 to 4 μm.
[0033] According to the present invention, the thickness of the appropriate coating layer has both high conductivity and can avoid capacity loss caused by a decrease in the proportion of active materials. At the same time, the ionic conductivity is high, which can improve the rate performance of the battery. If the thickness of the coating layer is too small, it may affect the conductivity, increase the impedance, and reduce the gram capacity and cycle performance; if the thickness of the first coating layer is too large, the conductivity effect may not be improved much, and as the Ni and Co metal content increases, it tends to be ternary and loses cost advantages. The thickness of the coating layer in the present invention can be 0.5 to 3 μm. Exemplarily, the thickness of the first coating layer can be any value among 0.5 μm, 1 μm, 2 μm and 3 μm, or any value within the range of any two of the above values. Preferably, the thickness of the first coating layer can be 0.8 to 1.5 μm.
[0034] According to the present invention, based on the total mass of the positive active material, the content of the lithium iron phosphate particles is 78-99.5wt%, and the content of the high nickel material is 0.5-22wt%. In the present invention, if the content of the lithium iron phosphate particles is too high, the thickness of the coating layer will be reduced, and it will be difficult to achieve the expected improvement in energy density and rate performance, and it will not be possible to maintain excellent cycle performance; if the content of the lithium iron phosphate particles is too low, it will lead to the loss of the cost advantage of the LFP matrix; if the content of the high nickel material is too high, it will tend to be ternary, and the cost and the cycle advantage brought by the stable olivine structure of LFP will be lost; if the content of the high nickel material is too low, it will lead to a decrease in conductivity, an increase in impedance, and a deterioration in gram capacity and cycle performance. Preferably, based on the total mass of the positive active material, the content of the lithium iron phosphate particles is 90-99wt%, and the content of the high nickel material is 1-10wt%.
[0035] According to the present invention, the organic boron additive can be selected from at least one of isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate), tetramethyl borate, trimethyl borate and trimethylcyclotriboroxane. As a preferred embodiment of the present invention, the organic boron additive is isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane. As an organic boron additive, isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane can be deposited to form a new layer to compensate for the failed film, which will not disappear with the cycle, and the rate performance of the battery can be simultaneously guaranteed.
[0036] According to the present invention, based on the total volume of the electrolyte, the content of the positive electrode film-forming additive can be 0.5-5 vol%. In the present invention, if the content of the positive electrode film-forming additive is too high, the film thickness will be too thick, the Li escape migration path inside the positive electrode material will be longer, the gram capacity will be slightly reduced, and the lithium ion diffusion impedance will be increased; if the content of the positive electrode film-forming additive is too low, the surface film will be uneven, and a dense CEI film will not be formed in part, resulting in Ni on the surface of the positive electrode material. 4+ The electrolyte has a side reaction, resulting in increased gas production, increased impedance, and poor cycle stability. Preferably, based on the total volume of the electrolyte, the content of the positive electrode film-forming additive may be 1.0 to 3 vol%.
[0037] In the present invention, the electrolyte may further include an electrolyte, a negative electrode film-forming additive and an organic solvent; optionally, in the electrolyte, the molar concentration of the electrolyte is 0.1 to 4.0 mol / L; optionally, based on the total volume of the electrolyte, the content of the negative electrode film-forming additive is 0.5 to 5 vol%, preferably 1.0 to 3.0 vol%.
[0038] According to the present invention, the electrolyte may be a lithium salt; illustratively, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorobis(oxalatophosphate).
[0039] According to the present invention, the organic solvent may include at least one of carbonate solvents, carboxylate solvents, ether solvents, sulfone solvents, nitrile solvents, fluorocarbonate solvents, fluorocarboxylate solvents, fluoroether solvents and fluorosulfone solvents; preferably, the organic solvent may be selected from at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl formate, ethylene glycol dimethyl ether and fluoroacetonitrile.
[0040] According to the present invention, a suitable negative electrode film-forming additive has the effect of forming a stable solid electrolyte interface (SEI) film to print lithium dendrite production. In the present invention, the negative electrode film-forming additive may include at least one of vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate and vinyl sulfate.
[0041] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources. Preparation Examples 1 to 5 and Comparative Preparation Example 1 in the present invention are used to illustrate the preparation methods of different positive electrode active materials used in the examples and comparative examples.
[0042] Preparation Example 1
[0043] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is a high-nickel material, and the high-nickel material is LiNi 0.83 Co 0.11 Mn 0.06 O2, the D50 of the lithium iron phosphate particles is 2μm, the coating layer accounts for 5wt% of the positive electrode active material, and the thickness of the coating layer is 1μm.
[0044] The positive electrode active material provided in this preparation example is prepared by the following steps:
[0045] (1) A high-nickel mixed solution was prepared using Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Co(CH3COO)2·4H2O with a molar ratio of 0.83:0.11:0.06.
[0046] (2) Under a nitrogen atmosphere, NaOH was added to the ternary mixed solution until a colloidal precipitate was completely formed and heated in a water bath at 80°C for 8 hours. The product was then precipitated for 24 hours to obtain a ternary precursor.
[0047] (3) Lithium hydroxide monohydrate and the ternary precursor are mixed and ball-milled to a material particle size D50 of 0.4 μm, and then calcined at 650° C. for 15 hours to obtain a ternary material (NCM) with a particle size D50 of 300 nm; wherein the ball milling operation satisfies the requirements, the ball milling temperature is 35° C., and the ball milling time is 10 hours.
[0048] (4) The mass ratio of LFP and NCM was 95%:5%. Commercial LFP was mixed with high nickel and then ball-milled. The mixture was calcined at 800 °C for 9 h in a pure oxygen atmosphere to obtain LFP@NCM material, which was recorded as positive electrode material A1.
[0049] Preparation Example 2
[0050] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is a high-nickel material, and the high-nickel material is LiNi 0.97 Co 0.02 Mn 0.01 O2, the D50 of the lithium iron phosphate particles is 2μm, the coating layer accounts for 5wt% of the positive electrode active material, and the thickness of the coating layer is 1μm.
[0051] The preparation method of the positive electrode active material in this preparation example is the same as that in Preparation Example 1, except that:
[0052] In the process of preparing the positive electrode material, the molar ratio of Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Co(CH3COO)2·4H2O is 97:2:1. The positive electrode active material prepared in Preparation Example 2 is recorded as positive electrode material A2.
[0053] Preparation Example 3
[0054] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is a high-nickel material, and the high-nickel material is LiNi 0.7 Co 0.1 Mn 0.2 O2, the D50 of the lithium iron phosphate particles is 2μm, the coating layer accounts for 5wt% of the positive electrode active material, and the thickness of the coating layer is 1μm.
[0055] The preparation method of the positive electrode active material in this preparation example is the same as that in Preparation Example 1, except that:
[0056] In the process of preparing the positive electrode material, the molar ratio of Ni(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and Co(CH3COO)2·4H2O is 70:10:20. The positive electrode active material prepared in Preparation Example 3 is recorded as positive electrode material A3.
[0057] Preparation Example 4
[0058] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is a high-nickel material, and the high-nickel material is LiNi 0.83 Co 0.11 Mn 0.06 O2, the D50 of the lithium iron phosphate particles is 2μm, the coating layer accounts for 0.5wt% of the positive electrode active material, and the thickness of the coating layer is 0.2μm.
[0059] The preparation method of the positive electrode active material in this preparation example is the same as that in Preparation Example 1, except that:
[0060] The mass ratio of LFP to NCM was 99.5%:0.5%. Commercial LFP was mixed with high nickel and then ball milled, and calcined at 800°C for 9 hours in a pure oxygen atmosphere to obtain LFP@NCM material. The positive electrode active material obtained in Preparation Example 4 was recorded as positive electrode material A4.
[0061] Preparation Example 5
[0062] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is a high-nickel material, and the high-nickel material is LiNi 0.83 Co 0.11 Mn 0.06 O2, the D50 of the lithium iron phosphate particles is 2μm, the coating layer accounts for 15wt% of the positive electrode active material, and the thickness of the coating layer is 2μm.
[0063] The preparation method of the positive electrode active material in this preparation example is the same as that in Preparation Example 1, except that:
[0064] The mass ratio of LFP to NCM was 85%:15%. Commercial LFP was mixed with high nickel and then ball milled. The mixture was calcined at 800°C for 9 hours in a pure oxygen atmosphere to obtain LFP@NCM material. The positive electrode active material obtained in Preparation Example 5 was recorded as positive electrode material A5.
[0065] Comparative Preparation Example 1
[0066] This preparation example provides a positive electrode active material, which includes a core particle and a coating layer arranged on the surface of the core, the material constituting the core particle is lithium iron phosphate, the material constituting the coating layer is carbon, the particle size of the lithium iron phosphate particle is 2μm, the coating layer accounts for 1wt% of the positive electrode active material, and the thickness of the coating layer is 1μm.
[0067] 10% glucose was added to the obtained LFP, and the two were completely ground with a ball mill for 3 hours. Subsequently, it was transferred to a vacuum tube furnace and the temperature was increased by 3°C / min to 750°C for 8 hours to obtain a carbon-coated sample named LFP@C. The positive electrode active material obtained in Comparative Preparation Example 1 was recorded as positive electrode material D1.
[0068] Example 1
[0069] The preparation method of the lithium ion battery in this embodiment includes:
[0070] (1) The positive electrode material powder, conductive carbon, carbon nanotubes and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95.2:1:0.8:3, and then N-methylpyrrolidone (NMP) was added in a high-speed mixer and uniformly mixed into a slurry with a solid content of 74%. The slurry was coated on one side of an aluminum foil with a thickness of 12 microns using a transfer coater and dried, and the weight of the coating per unit area after drying was maintained at 22.5 mg / cm 2 Then, the same process is adopted on the other side of the aluminum foil to coat and dry to obtain a semi-finished positive electrode sheet.
[0071] (2) Artificial graphite powder, conductive carbon, CMC (sodium carboxymethyl cellulose) and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 94:1:2:2, and then deionized water was added in a high-speed mixer and uniformly mixed into a slurry with a solid content of 48%. The slurry was coated on one side of a copper foil with a thickness of 8 μm using a transfer coater and dried, maintaining a coating weight per unit area of 10.4 mg / cm after drying. 2 Then, the same process is adopted on the other side of the copper foil to coat and dry to obtain a negative electrode semi-finished product.
[0072] (3) The exposed metal foil of the electrode is processed and welded into an electrode ear, and then wound with a separator to form a winding core. The winding core is wrapped with an aluminum-plastic film to form a semi-finished battery cell, which is dried and then injected with electrolyte. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0073] The positive electrode material powder used in the preparation method of the lithium ion battery of this embodiment is positive electrode material A1, the organic solvent contained in the electrolyte is a solvent obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1; the lithium salt contained in the electrolyte is 1 mol / L LiPF6; the negative electrode film-forming additive contained in the electrolyte is vinylene carbonate, and the content of the negative electrode film-forming additive is 2 vol% based on the total volume of the electrolyte; the positive electrode film-forming additive contained in the electrolyte is isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane, and the content of the positive electrode film-forming additive is 2 vol% based on the total volume of the electrolyte.
[0074] Example 2
[0075] The preparation method of the lithium-ion battery in this embodiment is generally the same as that in Embodiment 1, except that the positive electrode material powder used in this embodiment is positive electrode material A2.
[0076] Example 3
[0077] The preparation method of the lithium-ion battery in this embodiment is generally the same as that in Embodiment 1, except that the positive electrode material powder used in this embodiment is positive electrode material A3.
[0078] Example 4
[0079] The preparation method of the lithium-ion battery in this embodiment is generally the same as that in Embodiment 1, except that the positive electrode material powder used in this embodiment is positive electrode material A4.
[0080] Example 5
[0081] The preparation method of the lithium-ion battery in this embodiment is generally the same as that in Embodiment 1, except that the positive electrode material powder used in this embodiment is positive electrode material A5.
[0082] Comparative Example 1
[0083] The preparation method of the lithium-ion battery in this comparative example is generally the same as that in Example 1, except that the positive electrode material powder used in this comparative example is positive electrode material D1.
[0084] Comparative Example 2
[0085] The preparation method of the lithium-ion battery in this comparative example is generally the same as that in Example 1, except that the electrolyte used in this comparative example does not contain a positive electrode film-forming additive.
[0086] Comparative Example 3
[0087] The preparation method of the lithium-ion battery in this comparative example is the same as that in Example 1, except that the positive electrode film-forming additive contained in the electrolyte used in this comparative example is 1,3-propanesulfonate.
[0088] Comparative Example 4
[0089] The preparation method of the lithium-ion battery in this comparative example is generally the same as that in Example 1, except that the positive electrode film-forming additive contained in the electrolyte used in this comparative example is acetonitrile.
[0090] The positive electrode active material and positive electrode film-forming additive components included in the lithium ion batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 4 of the present invention are shown in Table 1, wherein ITD represents isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane, PS represents 1,3-propanesulfonate, ACN represents acetonitrile, and the content of the positive electrode film-forming additive is the volume fraction based on the total volume of the electrolyte.
[0091] Table 1
[0092]
[0093] Test Example 1
[0094] The lithium ion batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to relevant battery performance tests. The test results are shown in Table 2.
[0095] Among them, battery performance tests include:
[0096] (1) Discharge specific capacity
[0097] At 25°C, let the lithium-ion battery stand for 30 minutes and then discharge it at a constant current of 0.5C to a voltage of 2.5V. Charge the lithium-ion battery at a constant current of 0.33C to a voltage of 4.2V, and then charge it at a constant voltage to a current ≤0.05C. Record the first cycle charge and discharge capacity, and calculate the discharge specific capacity based on the weight of the positive electrode.
[0098] (2) DCR test
[0099] 25 degrees 50% SOC DCR test 2C rate discharge 30 seconds to measure DCR (2C-30s 50% SOC DCR@25℃):
[0100] First, test the 1C capacity. Place the lithium-ion battery in a constant temperature environment of 25℃ for 1h, use the nominal capacity for 1C / 1C charging and discharging, charge at a constant current of 1C to a voltage of 4.2V, then charge at a constant voltage of 4.2V with a cut-off current of 0.05C, and then discharge at a constant current of 1C to 2.5V after standing for 15min. The discharge capacity is the 1C capacity C0; then adjust the SOC to 50%, charge at a constant current of 1C0 to a voltage of 4.2V, then charge at a constant voltage of 4.2V with a cut-off current of 0.05C0, and then discharge at a constant current of 1C0 for 30min after standing for 15min. 25℃50%SOC DCR test: The lithium-ion battery is placed in a constant temperature environment of 25℃ for 2h, and discharged at 1C0 for 30s. The voltage in the last second before discharge is recorded as V1, and the voltage for 30s of discharge is recorded as V2. The discharge DCR of 25℃50%SOC is (V1-V2) / (2C0).
[0101] -20℃50%SOC DCR test: 0.36C rate discharge for 30 seconds to measure DCR (0.36C-30s 50%SOC DCR@-20℃):
[0102] After 1C0 constant current charging to a voltage of 4.2V, the charging cut-off current is 0.05C0 at a constant voltage of 4.2V. After standing for 15min, the 1C0 constant current discharge is performed for 30min. The lithium-ion battery is stood in a constant temperature environment of -20℃ for 2h, discharged at 1C for 30s, and the voltage before discharge in the last second is recorded as V1, and the voltage of discharge for 30s is recorded as V2. The discharge DCR of 50% SOC at -20℃ is (V1-V2) / (0.36C0).
[0103] (3) 25 degree cycle performance test:
[0104] First, in an environment of 25°C, the first charge and discharge were carried out. After constant current charging at a charging current of 1C to a voltage of 4.2V, the charging cut-off current was 0.05C at a constant voltage of 4.2V. After standing for 15 minutes, constant current discharge was carried out at a discharge current of 1C to 2.5V. The discharge capacity of the first cycle was recorded as C1. Then, charge and discharge cycles were carried out until the capacity decayed to 80% C1, and the number of cycles corresponding to the 80% discharge capacity retention rate of 80% was recorded.
[0105] (4) 45 degree cycle performance test:
[0106] First, in an environment of 45°C, the first charge and discharge were carried out. After constant current charging at a charging current of 1C to a voltage of 4.2V, the charging cut-off current was 0.05C at a constant voltage of 4.2V. After standing for 15 minutes, constant current discharge was carried out at a discharge current of 1C to 2.5V. The discharge capacity of the first cycle was recorded as C1. Then, charge and discharge cycles were carried out until the capacity decayed to 80% C1, and the number of cycles corresponding to the 80% discharge capacity retention rate of 80% was recorded.
[0107] Table 2
[0108]
[0109] It can be seen from Table 1 that Examples 1 to 3 compare the effects of different Ni, Co, and Mn contents in high-nickel materials in the positive electrode active material on the overall battery performance. 4+ Too high content, Ni 4+ The activity is strong and the structure is unstable. It is easy to deoxidize and react with the electrolyte, and the layered structure is converted into a rock salt phase structure, thereby increasing the impedance and causing the cycle effect to deteriorate. The Ni content in the coating layer of Example 3 is low, the conductivity is relatively poor, and the impedance is high. It cannot achieve the conductivity improvement of the LFP material brought by the C coating, resulting in relatively poor overall electrical performance.
[0110] Examples 1, 4, and 5 compare the effects of different coating thicknesses of the coating layer in the electrode active material on the overall battery performance. The coating thickness of the coating layer in Example 1 is 1 μm. The coating thickness in Example 4 is 0.2 μm, which is too low and has a poor coating effect, and cannot achieve the effect of improving the conductivity of lithium iron phosphate. At the same time, the overall impedance is high, and the gram capacity, rate, and cycle equalization performance will deteriorate. The thickness of the coating layer in Example 5 is 2 μm, which causes the material to tend to be ternary, losing the cost advantage and the cycle advantage brought by the stable olivine structure of lithium iron phosphate.
[0111] The positive electrode material used in Comparative Example 1 is conventional carbon coating, and the thickness of the carbon coating is the same as the thickness of the first coating layer. Comparing Example 1 with Comparative Example 1, Example 1 has improved gram capacity, rate, and cycle. This is mainly because the coating layer in Example 1 is a high-nickel material with activity, while carbon is inactive.
[0112] Example 1 and Comparative Examples 2 to 4 compare the effects of different positive electrode film-forming additives on the overall battery performance. In Example 1, the positive electrode film-forming additive is isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane; in Comparative Example 2, no positive electrode film-forming additive is used, in Comparative Example 3, the positive electrode film-forming additive is 1,3-propanesulfonic acid lactone, and in Comparative Example 4, the positive electrode film-forming additive is acetonitrile. Compared with Comparative Examples 2 to 4, Example 1 uses an organic boron additive as a positive electrode film-forming additive. The higher occupied molecular orbital (HOMO) energy can decompose the solvent to generate a boron-containing CEI, thereby inhibiting the dissolution of nickel, maintaining a complete high-nickel form, reducing the self-discharge rate, and isolating the highly active Ni 4+ The valence substances react with HF in the electrolyte to ensure cycle stability.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material; The positive electrode active material includes lithium iron phosphate particles and a coating layer coated on the surface of the lithium iron phosphate particles; the coating layer contains a high-nickel material, and the high-nickel material includes LiNi x Co y Mn z O2, where x+y+z=1, 0.80≤x≤0.95, 0.0 <y<0.20,0.0<z<0.20; The electrolyte includes a positive electrode film-forming additive, and the positive electrode film-forming additive includes an organic boron additive.
2. The lithium-ion battery according to claim 1, characterized in that The D50 of the lithium iron phosphate particles is 0.7 to 6 μm, preferably 1 to 4 μm.
3. The lithium-ion battery according to claim 1, characterized in that The coating layer has a thickness of 0.5 to 3 μm, preferably 0.8 to 1.5 μm.
4. The lithium-ion battery according to claim 1, characterized in that: Based on the total mass of the positive electrode active material, the content of the lithium iron phosphate particles is 78-99.5wt%, and the content of the high nickel material is 0.5-22wt%; Preferably, based on the total mass of the positive electrode active material, the content of the lithium iron phosphate particles is 90-99wt%, and the content of the high-nickel material is 1-10wt%.
5. The lithium-ion battery according to claim 1, characterized in that: The organic boron additive is selected from at least one of isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate), tetramethyl borate, trimethyl borate and trimethylcyclotriboroxane; Preferably, the organic boron additive is isopropoxy-4,4,5,5-tetramethyl-1,3,2-dioxaborane.
6. The lithium-ion battery according to claim 1, characterized in that Based on the total volume of the electrolyte, the content of the positive electrode film-forming additive is 0.5 to 5 vol%, preferably 1.0 to 3 vol%.
7. The lithium-ion battery according to claim 1, characterized in that: The electrolyte also includes an electrolyte, a negative electrode film-forming additive and an organic solvent; Optionally, in the electrolyte, the molar concentration of the electrolyte is 0.1 to 4.0 mol / L; Optionally, based on the total volume of the electrolyte, the content of the negative electrode film-forming additive is 0.5 to 5 vol%, preferably 1.0 to 3.0 vol%.
8. The lithium-ion battery according to claim 7, characterized in that: The electrolyte is a lithium salt; Optionally, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorobis(oxalatophosphate).
9. The lithium-ion battery according to claim 7, characterized in that: The organic solvent comprises at least one of carbonate solvents, carboxylate solvents, ether solvents, sulfone solvents, nitrile solvents, fluorinated carbonate solvents, fluorinated carboxylate solvents, fluorinated ether solvents and fluorinated sulfone solvents; Preferably, the organic solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl formate, ethylene glycol dimethyl ether and fluoroacetonitrile.
10. The lithium ion battery according to claim 7, characterized in that: The negative electrode film-forming additive includes at least one of vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate and vinyl sulfate.
Citation Information
Patent Citations
Fe base lithium sale compound anode materials and its making method
CN101188293A
Lithium iron phosphate cathode composite material and preparation method thereof
CN106953073A
Electrolyte for high-nickel ternary positive electrode material system battery and lithium ion battery
CN110148774A
Electrolyte for lithium ion battery, lithium ion battery, battery module, battery pack and device
CN110783626A
Electrolyte additive, electrolyte and lithium ion battery
CN111682264A